Geographic Information System (GIS) as Tool to Manage the Impacts of Flood in Shah Alam, Malaysia - Leeonis Adam Narashman; Ahmed Minhaz Farid; Mokhtar Mazlin (E3S Web of Conferences)
Floods, common in lowland regions, pose significant environmental, social, and economic challenges, as seen in Shah Alam’s severe flooding in 2021. While GIS offers promising solutions, there remain shortcomings in flood disaster recovery efforts. This study investigated how the Geographic Information System (GIS) could help manage the environmental impacts of floods in Shah Alam, Malaysia. Reaserch method for this study using thematic analysis, qualitative methods, an informal interview of experts following the quadruple helix model, were used to select 20 respondents from four key sectors: government, academia, business, and community/NGO, to explore the use of GIS in flood management. While progress has been made, challenges persist, highlighting the need for enhanced flood preparedness and infrastructure. The result shows there is government initiatives, such as CCTV installations by MBPJ, demonstrate proactive measures to mitigate flood impacts. Overall, this study highlights the importance of effective GIS applications in addressing flood vulnerabilities and calls for further improvements in flood management strategies in Shah Alam, Malaysia.